Imagining the future with citizens: participatory foresight and democratic policy design in Marcoussis, France. Issue 1 (2nd January 2022) - Gouache, Christophe
Abstract: The idea that the future is too serious and strategic to be discussed with people who are not "experts" is so commonly shared that citizens' voices are lacking in most decision-making processes and future-oriented choices whether we look at political or research and innovation agendas. Yet, proofs to contradict this vision are now multiplying and can be found in a growing number of case studies and scientific publications. Citizens are proving not only to be legitimate actors to contribute to the future agenda-setting of local, national or European levels but also relevant and pertinent contributors. However, this practice of participatory agenda-setting—even though it is getting greater attention—remains relatively experimental, atypical and sporadic. The limits and drawbacks of citizen participation processes have already been highlighted in the literature but rather than calling this practice to an end it actually calls for more experimentation as the difficulties do not diminish the democratic need, legitimacy and value of such governance practices. Especially, since many western democracies are becoming very fragile. We will see in the preliminary part of this paper, the many challenges that undermine not only the functioning of democratic processes but also the citizens' role and sense of agency in the governance of the society they live in, as well as the role of elected officials and experts regarding agenda-setting, then we will look into the lack of future thinking not only in the political sphere but also the educational and social practices, analyze the values of participatory processes and its potential limits and risks and finally review an experimental case of participatory foresight and policy design from the small town of Marcoussis (France) which successfully conducted a participatory agenda-setting experiment—and voted—after a 2 years-long process, their local agenda for the future together with its inhabitants, civil servants and elected officials. Marcoussis has engaged around 600 people (out of a population of 8000 inhabitants) in 25 moments, using very diverse methods and techniques (forum-theater, philosophy talks, market of ideas for the future, collective distillation) and setting the process in unusual and non-administrative contexts (entering into schools, 'hacking' their local popular festivals) to touch a very diverse set of citizens and gather as many contributions as possible. In this case analysis, we will inspect the preliminary conditions of how Marcoussis set up their participatory foresight and agenda-setting process, then review the creative tools and design methods that were experimented and finally, draw the lessons learned in terms of participatory agenda-setting processes and democratic innovations.